Taeniasis and cysticercosis prevalence in a small village from Northeastern Brazil Prevalência de teníase e sorologia positiva para cisticercose em Mulungu do Morro, Bahia - Irenio Gomes; Marielza Veiga; Emília Katiane Embiruçu; Rosângela Rabelo; Bernardo Mota; Antonio Meza-Lucas; Raquel Tapia-Romero; Bertha Laura Carrillo-Becerril; Isabel Alcántara-Anguiano; Dolores Correa; Ailton Melo (Arquivos de Neuro-Psiquiatria)
Although not considered as an endemic region, the Northeast of Brazil has the necessary conditions for the development of taeniasis-cysticercosis complex. In a previous paper, we demonstrated that Mulungu do Morro municipality, in the State of Bahia, has a high seroprevalence to cysticercosis in epileptic patients. OBJECTIVE: to determine the prevalence of taeniasis and positive cysticercosis serology in the population of Mulungu do Morro. METHOD: blood and stool samples were collected from a random sampling of the population, by family. The identification of antibodies against T. solium cysticerci was made by EITB and T. solium antigens were identified using a polyclonal antibody-capture ELISA. RESULTS: the cysticercosis seroprevalence was 1.6% (C.I. = 0.8 to 2.8%) and the taeniasis prevalence 4.5% (C.I. = 3.0 to 6.5%). Seropositivity to cysticercosis was higher among those who lived in a house of a person testing positive for coproantigen, p=0.017. CONCLUSION: our results demonstrate that the taeniasis-cysticercosis complex is endemic in Mulungu do Morro. We believe that all areas in the world with the same socio-economic and sanitary characteristics are likely to have high prevalence of this parasite. Embora alguns autores não a considerem uma região endêmica, existem no Nordeste do Brasil as condições necessárias para o desenvolvimento do complexo teníase/ cisticercose. Em uma publicação prévia demosntramos no município de Mulungu do Morro, Bahia, alta soroprevalência para cisticercose em pacientes epilépticos. OBJETIVO: determinar a prevalência de teníase e sorologia positiva para cisticercose na população de Mulungu do Morro. MÉTODO: foram coletadas amostras de sangue e fezes em 175 famílias definidas aleatoriamente. A identificação de anticorpos séricos anti-cisticerco foi feita através do método de EITB e a presença de teníase foi verificada através de ELISA de captura para identificação de antígenos do parasita nas fezes. RESULTADOS: encontramos soroprevalência para cisticercose de 1,6% (IC a 95% de 0,8 a 2,8%) e prevalência de teníase de 4,5% (IC a 95% de 3,0 a 6,5%). Foi observado maior número de soropositivos nas famílias em que havia uma pessoa com teníase (p=0,007). CONCLUSÕES: nossos resultados demonstram que Mulungu do Morro é endêmico para teníase e cisticercose. Acreditamos que os demais municípios do Nordeste, cujas características socio-econômicas e condições sanitárias são semelhantes ao estudado, apresentam também alta prevalência dessa parasitose e que estudos epidemiológicos são necessários para esta definição e para que medidas de controle sejam tomadas.